دور الأمواج فوق الصوتية في تشخيص عسر حركية المرارة - جركــس عامـر; قنجراوي أكثم; ناصــر محمـد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 25 مريضا مراجعا لقسم الاسعاف بمشفى الأسد الجامعي باللاذقية بين عامي 2009 - 2010 بشكاية ألم مراقي أيمن, أجري لهم تقييم سريري من قبل أطباء الجراحة والداخلية وتقييم مخبري إسعافي ثم تم إجراء تصوير بالأمواج فوق الصوتية قبل وبعد تناول وجبة دسمة مؤلفة من صفار البيض والحليب "تجربة الوجبة الدسمة" لتقييم الوظيفة التقلصية للمرارة, وذلك بهدف تشيص خلل حركية المرارة عند المرضى الذين يشكون من أعراض سريرية لقولنج مراري وإبراز الدور المشخص للتصوير بالأمواج فوق الصوتية في تشخيص عسر حركية المرارة الأمر الذي سيغني عن إجراءات تشخيصية غازية ومكلفة. تبين وجود عسر حركية مرارة لدى سبع 7 مرضى وألم مراقي أيمن بدون عسر حركية لدى مريضين ولم يتحرض هذا الألم نتيجة لهذا الفحص لبقية عينة الدراسة. أظهرت الدراسة الإحصائية لنتائج البحث وجود علاقة ضعيفة بين شدة الألم المراقي الأيمن وعسر حركية المرارة ولكنها طردية. A total of 25 patients were accepted in the ER of the University Al-Assad Hospital, Lattakia, in the period between 200–2010 with a chief complaint of right upper quadrant pain. The patient has undergone a clinical evaluation from the surgery and internal medicine residents, and quick laboratory tests were performed. Then, we made an ultrasonographic evaluation with the use of yolk and milk “fatty meal” to assess the contractility function of the gallbladder. So that we could diagnose biliary dyskinesia in patients complaining about clinical symptoms of biliary colic. We could also reveal the diagnostic role of ultrasonography in the diagnosis of biliary dyskinesia. Hence, we can avoid many invasive and expensive diagnostic maneuvers. We found that 7 patients out of the whole group have a biliary dyskinesia and 2 patients out of the whole group have upper quadrant pain without a biliary dyskinesia. This statistical study has shown that there is a weak relation between upper quadrant pain and biliary dyskinesia while there is a direct correlation between these two factors.